A bug reproduction approach based on directed model checking and crash traces. Issue 3 (18th May 2016) - Nayrolles, Mathieu; Hamou‐Lhadj, Abdelwahab; Tahar, Sofiène; Larsson, Alf
Abstract: Reproducing a bug that caused a system to crash is an important task for uncovering the causes of the crash and providing appropriate fixes. In this paper, we propose a novel crash reproduction approach that combines directed model checking and backward slicing to identify the program statements needed to reproduce a crash. Our approach, named JCHARMING (Java CrasH Automatic Reproduction by directed Model checkING), uses information found in crash traces combined with static program slices to guide a model checking engine in an optimal way. We show that JCHARMING is efficient in reproducing bugs from 10 different open source systems. Overall, JCHARMING is able to reproduce 80% of the bugs used in this study in an average time of 19 min. Copyright © 2016 John Wiley & Sons, Ltd.